Role of Maintenance Gemcitabine in Advanced Carcinoma Gallbladder - Sharma, Manish; Talwar, Vineet; Maheshwari, Udip; Koyyala, Venkata Pradeep Babu; Goel, Varun; Goyal, Sumit; Dash, Prasanta Kumar; Batra, Ullas; Bajaj, Rajat; Yadav, Abhishek; Goyal, Pankaj; Doval, Dinesh Chandra (South Asian Journal of Cancer, 2020)
Objective The aim of this study is to investigate the effects of gemcitabine maintenance on progression-free survival (PFS) in patients with metastatic gallbladder cancer (GBC).Materials and Methods Sixty patients with unresectable or metastatic GBC having ongoing response to treatment with initial six cycles of gemcitabine and a platinum-based doublet chemotherapy were prospectively randomized on day 21 of the 6th cycle in 1:1 fashion to receive either maintenance gemcitabine 1 g/m2 intravenously on day 1 and day 8 of three weekly cycle or observation. Survival analysis was performed using the Kaplan–Meier method and comparisons by the log-rank test. A p-value < 0.05 was considered as statistically significant.Results Of 60 patients, a total of 56 were available for final analysis. The median PFS was 4.7 months (3.1–6.3) in gemcitabine arm and 2.6 months (2.4–2.8) in observation arm, hazard ratio (HR) 0.196 (95% confidence interval [CI]: 0.1–0.39), p < 0.001. Median overall survival in gemcitabine arm was 12.4 months (9.15–15.6) as opposed to 9.9 months (8.29–11.5) in observation arm, HR 0.76 (95% CI: 0.43–1.35), p = 0.354. The grade 3 or 4 side effects in maintenance arm were transaminitis (17.9%), thrombocytopenia (17.8%), neutropenia (14.2%), and febrile neutropenia (7.1%).Conclusions Maintenance gemcitabine therapy in unresectable/metastatic GBC patients responding to first-line gemcitabine and platinum treatment contributes to increase PFS with minimal and manageable side effects.
Keywords: gallbladder cancer; gemcitabine; maintenance; progression-free survival